Ferritic stainless steel sheet
Patent Information
- Application Number
- JP2023148616
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0012】 本発明により、溶接後の硬質化を抑制し、靭性に優れた板厚5mm以上のフェライト系ステンレス鋼板を得ることができる。なお、本鋼板は高剛性と高精度の形状管理が要求される締結部品用などに適用することができる。
Smart Images

Figure 2025041364000001 
Figure 2025041364000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel sheet, which is believed to be optimal for fastening part applications that require high rigidity and highly accurate shape control. [Background technology]
[0002] Ferritic stainless steels are used in many applications because they are cheaper than austenitic stainless steels, which contain a lot of expensive Ni. As a specific example, automotive exhaust gas path components are composed of various parts such as exhaust manifolds, catalysts, and mufflers, and fasteners called flanges are used to connect these parts. To ensure rigidity, thick flanges over 5mmt are used, and the flanges and parts are often joined by welding. For this reason, it is also required to ensure corrosion resistance of the welded parts. However, since carbon and nitrogen are difficult to dissolve in the ferritic phase, Cr carbonitrides are formed due to the heat effect during welding, causing a decrease in corrosion resistance called sensitization. For this reason, Ti or Nb, which has a stronger bond with carbon and nitrogen than Cr, may be added.
[0003] On the other hand, ferritic stainless steel has low toughness, and when the plate thickness is large, it is prone to cracking during steel strip manufacturing and processing. In particular, Ti-containing ferritic stainless steel is known to have coarse TiN crystallization during solidification, which significantly reduces toughness.
[0004] As a means for improving the toughness of ferritic stainless steel, for example, Patent Document 1 discloses a ferritic stainless steel in which coarse TIN precipitation, which is a cause of a decrease in toughness, is avoided by adding Zr. Patent Document 2 discloses a ferritic stainless steel in which Ti is substantially not added and particulate matter other than the ferritic phase is specified. Furthermore, Patent Document 3 discloses a technology in which the Cr and Ni contents are controlled within an appropriate range to generate austenite and ferritic phases in a hot rolling process, and then hot rolling is performed, followed by annealing the hot-rolled sheet at an appropriate temperature range in the ferritic single phase temperature range. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-225944 A [Patent Document 2] International Publication No. 2020 / 084987 Summary of the Invention [Problem to be solved by the invention]
[0006] In ferritic stainless steel, when processing such as shape modification or bending after welding, especially when the plate thickness is thick, thermal strain due to temperature distribution during welding is large, and processing such as shape modification and bending increases in frequency. During such processing after welding, brittle cracks may occur due to insufficient toughness, including in the welded part.
[0007] However, although Patent Document 1 attempts to improve toughness, since Ti is not added, the welded portion during welding may become hard due to solid solution strengthening of nitrogen, resulting in insufficient toughness. Patent Document 2 also suggests that martensite structure is generated after welding, which may result in insufficient toughness due to hardening. In other words, the prior art document invention attempts to improve toughness, but does not consider brittle fracture due to hardening after welding.
[0008] The present invention provides a ferritic stainless steel sheet having a thickness of 5 mm or more, which can suppress hardening after welding while ensuring a certain level of toughness. In this specification, unless otherwise specified, a certain level of toughness refers to good toughness as evaluated by a Charpy impact test described later. The suppression of hardening after welding is evaluated by the cross-sectional hardness after welding described later. [Means for solving the problem]
[0009] In the present invention, in order to suppress hardening after welding, the inventors conducted extensive research into manufacturing conditions and structural forms that can ensure toughness even in a state where coarse TiN precipitates are present in a ferritic stainless steel containing an appropriate range of Ti. As a result, they discovered that by limiting the range of components and strictly controlling the hot rolling conditions, it is possible to suppress hardening after welding while ensuring a certain level of toughness.
[0010] Specifically, the inclusion of 8 (C+N) or more Ti suppresses hardening of the welded zone. Furthermore, by tightening the slab extraction temperature and rough hot rolling conditions in hot rolling to refine the structure before finish hot rolling, and then tightening the reduction amount, interpass time, and coiling temperature in finish hot rolling to allow the processing strain introduced during hot rolling to remain after finish hot rolling, the inclusion of a trace amount of Nb suppresses grain growth, refines the average crystal grain size after hot rolling annealing to 30 μm or less, and it was discovered that a certain level of toughness can be secured even in Ti-containing ferritic stainless steel.
[0011] The present invention has been made based on the above findings and further studies, and the gist of the present invention is the following ferritic stainless steel sheet. (1) Chemical composition, in mass%, C: 0.002 to 0.030%, Si: 0.10 to 1.00%, Mn: 1.0% or less, P: 0.040% or less, S: 0.0300% or less, Cr: 10.0-19.0%, Nb: 0.05-0.15%, Ti: 8×(C%+N%)~0.40%, N: 0.002~0.030%, Ni: 0 to 0.50%, Mo: 0-2.50% Cu: 0-0.60% V: 0~0.50%, W: 0 to 0.50%, Co: 0-0.50%, Zr: 0-0.50%, Al: 0-1.00%, Sn: 0-0.50%, B: 0~0.0050%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, REM: 0~0.0100% The balance is Fe and impurities. The ferritic stainless steel plate has an average crystal grain size of 30 μm or less and a thickness of 5 mm or more. In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. That is, C% represents the C content, and N% represents the N content. (2) The chemical composition is, in mass%, Ni: 0.01 to 0.50%, Mo: 0.01 to 2.50% Cu: 0.01 to 0.60% V: 0.01 to 0.50%, W: 0.01 to 0.50%, Co: 0.01 to 0.50%, Zr: 0.01 to 0.50%, Al: 0.01 to 1.00%, Sn: 0.01 to 0.50%, B: 0.0002~0.0050%, Ca: 0.0002~0.0100%, Mg: 0.0002~0.0100%, REM: 0.0002~0.0100% The ferritic stainless steel sheet according to the above (1), comprising one or more selected from the following: (3) A ferritic stainless steel sheet according to (1) or (2) above, which is a sheet annealed after hot rolling. (4) A steel having the chemical composition described in (1) or (2) above is melted to produce a slab; The slab is heated to a temperature in the range of 1150 to 1250°C and subjected to hot rolling including rough hot rolling and finish hot rolling. In the rough hot rolling, the slab is rolled at a total rolling reduction of 80% or more, the final temperature of the rough hot rolling is 1050 ° C. or more, and the interpass time from the completion of the rough hot rolling to the start of the finish hot rolling is 30 seconds to 90 seconds; In the finish hot rolling, the inter-pass time after each rolling reduction is 5 seconds or less, the total rolling reduction rate is 70% or more, the final temperature of the finish hot rolling is 900°C or less, and the coiling temperature is 450°C or less. A method for manufacturing a ferritic stainless steel sheet, comprising performing hot rolling annealing on the hot rolled sheet under the conditions of 850°C to 920°C within 1 minute after the hot rolling.
Effect of the Invention
[0012] According to the present invention, it is possible to obtain a ferritic stainless steel sheet having a thickness of 5 mm or more, which suppresses hardening after welding and is excellent in toughness. In addition, this steel sheet can be applied to fastening parts that require high rigidity and high-precision shape control.
Embodiments for Carrying out the Invention
[0013] Hereinafter, each component will be described in detail. Unless otherwise specified, "%" regarding the components indicates mass% in the steel. When the lower limit is not particularly defined or the lower limit is 0%, it includes the case of not containing (0%).
[0014] <C: 0.002 to 0.030%> Since C deteriorates formability and corrosion resistance, the upper limit is set to 0.030% or less, and it may be 0.020% or less, 0.015%. From the viewpoints of formability and corrosion resistance, it is preferable to lower C, but in existing steelmaking facilities, reducing the C content to less than 0.002% causes a large increase in cost. Therefore, the lower limit of C is set to 0.002%, preferably 0.003%.
[0015] <Si: 0.10 to 1.00%> Si is an element useful as a deoxidizer and also an element that improves oxidation resistance, and its effect is exhibited at 0.10% or more. Preferably, it may be 0.15% or more. However, excessive inclusion causes hardening and reduces cold rolling ductility. Therefore, in the present invention, the upper limit is set to 1.00%. Preferably, 0.60% is desirable.
[0016] <Mn: 1.0% or less> Mn is an element contained as a deoxidizer and forms on the surface of the Mn-based oxide during long-term use, contributing to the improvement of scale adhesion. Mn may be 0%, but in order to obtain the above-described effects, 0.1% or more is preferable. More preferably, it is 0.2% or more. However, excessive content not only significantly increases the oxidation increment but also makes it easier for the γ phase to be generated at high temperatures. Therefore, in the present invention, the upper limit is set to 1.0% or less. Preferably, it is 0.8% or less.
[0017] <P: 0.040% or less> P is a harmful element that reduces toughness, and it is desirable to reduce it as much as possible. Therefore, in the present invention, the amount of P is set to 0.040% or less. Preferably, it is 0.030% or less.
[0018] <S: 0.0300% or less> S is also a harmful element that reduces elongation, adversely affects formability and toughness, and reduces corrosion resistance. Therefore, it is desirable to reduce it as much as possible. Thus, in the present invention, the amount of S is set to 0.0300% or less. Preferably, it is 0.0100% or less. More preferably, it is 0.0050% or less.
[0019] <Cr: 10.0 - 19.0%> Cr is an important element effective for improving the corrosion resistance and oxidation resistance, which are the characteristics of stainless steel, and its effect is manifested at 10.0% or more. The preferable lower limit value is 10.5%. On the other hand, Cr is an element that solid-solution strengthens steel at room temperature, hardens it, and reduces ductility. In particular, when the content exceeds 19.0%, the toughness decreases and the adverse effect on formability becomes significant. Therefore, the upper limit is set to 19.0%, and preferably, it is 18.5%.
[0020] <Nb: 0.05 - 0.15%> Nb is an important element in the present invention. Nb easily forms carbonitrides with C and N, suppressing sensitization, while excessive content leads to a decrease in toughness due to the formation of Laves phase. In addition, since it inhibits workability, the upper limit is set to 0.15%, preferably 0.13%, more preferably 0.12%, even more preferably 0.11%, still more preferably 0.10%, and even more preferably 0.09%. On the other hand, the inclusion of Nb contributes to suppressing grain growth after recrystallization after rough hot rolling and after annealing of the hot-rolled sheet, and suppressing the recovery of strain introduced during finish hot rolling. Since these effects are manifested at 0.05% or more, the lower limit of the Nb content in the present invention is set to 0.05%, preferably 0.06%, more preferably 0.07%, and even more preferably 0.08%.
[0021] <Ti:8×(C%+N%)~0.40%> Ti has the effect of fixing C and N to improve corrosion resistance, formability, and intergranular corrosion resistance of welded parts. In the present invention, the upper limit of the Nb content is specified from the viewpoint of controlling toughness, so Ti is an important element for fixing C and N. In addition, Ti carbonitrides precipitated by fixing C and N become a source of strain field during hot rolling, contribute to the division of the rolled elongation structure, and contribute to the refinement of the average crystal grain size after hot rolling annealing. In addition, the precipitated Ti carbonitrides remain even after welding, and can suppress hardening after welding. In this specification, carbonitrides refer to compounds containing carbon or nitrogen, and may be compounds containing both carbon and nitrogen. In order to obtain this effect, a content of 8×(C%+N%) or more is required. Here, C% and N% in 8×(C%+N%) represent the content (mass%) of each element. If the content is less than this, C and N cannot be completely fixed, and sensitization and hardening of the welded part occur, resulting in a decrease in corrosion resistance and toughness. Therefore, the lower limit of the Ti content is set to 8 x (C% + N%), preferably 10 x (C% + N%), more preferably 11 x (C% + N%), and even more preferably 12 x (C% + N%). On the other hand, if the Ti content exceeds 0.40%, it induces a decrease in toughness and the occurrence of surface defects. Therefore, the upper limit of the Ti content is set to 0.40%, preferably 0.35%, more preferably 0.33%, even more preferably 0.32%, still more preferably 0.30%, and even more preferably 0.29%.
[0022] <N:0.002~0.030%> Like C, N deteriorates formability and corrosion resistance, so the lower the content, the better. Therefore, the upper limit is set to 0.030%, preferably 0.020%, and more preferably 0.015%. On the other hand, N precipitates as coarse and hard TiN at high temperatures, and contributes to the division of the rolled elongation structure due to the strain field around the precipitates during hot rolling. Since this effect is manifested at 0.002% or more, the lower limit of the N content in the present invention is set to 0.002%. However, since excessive reduction leads to an increase in refining costs, the lower limit of the N content is preferably 0.003%.
[0023] The effects of the present invention can be obtained with the above-mentioned composition, but the following elements may be contained as necessary. Since these elements are optional elements, the content of these elements in ferritic stainless steel may be 0%.
[0024] <Ni:0.01~0.50%> Ni is an element that improves the toughness of ferritic stainless steel, and in order to obtain this effect, it is preferable to contain 0.01% or more. On the other hand, Ni is an expensive element and a strong austenite phase forming element, so excessive Ni content increases the manufacturing cost of steel and makes it easier for γ phase to form at high temperatures. Therefore, in the present invention, the Ni content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0025] <Mo:0.01~2.50%> Mo is an element that improves corrosion resistance. In addition, it suppresses grain growth after rough hot rolling and hot rolling annealing, and contributes to suppressing the recovery of strain introduced during hot rolling. These effects are manifested at 0.01% or more, so the lower limit of Mo is preferably set to 0.01%. On the other hand, Mo is an expensive element, and since it hardens steel by solid solution strengthening, it reduces workability. Therefore, in the present invention, the content is set to 2.50% or less, preferably 2.30% or less, and more preferably 2.10% or less.
[0026] <Cu:0.01~0.60%> Cu is an element that strengthens the passive film and enhances corrosion resistance, and since this effect is manifested at 0.01% or more, the lower limit of Cu is preferably set to 0.01%, and more preferably to 0.02%. On the other hand, excessive Cu content precipitates as fine ε-Cu phase, which hardens the steel, so the upper limit of Cu is set to 0.60%, and preferably 0.50%.
[0027] <V:0.01~0.50%> Like Nb and Ti, V is a carbonitride-forming element, and contributes to suppressing grain growth by finely precipitating. To obtain this effect, it is preferable to contain 0.01% or more. On the other hand, excessive content leads to deterioration of manufacturability, so the content is set to 0.50% or less in the present invention. It is preferably 0.40% or less, and more preferably 0.30% or less.
[0028] <W:0.01~0.50%> Like Nb and Ti, W is a carbonitride forming element, and contributes to suppressing grain growth by finely precipitating. To obtain this effect, it is preferable to contain 0.01% or more. On the other hand, W is an expensive element, and an excessive content of W forms intermetallic compounds and reduces the toughness of steel, so in the present invention, the content is set to 0.50% or less. It is preferably 0.40% or less, and more preferably 0.30% or less.
[0029] <Co:0.01~0.50%> Co is an element that improves crevice corrosion resistance, and in order to obtain this effect, it is preferable to contain 0.01% or more. On the other hand, Co is an expensive element, and since it hardens steel by solid solution strengthening, it reduces workability. Therefore, in the present invention, the content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0030] <Zr:0.01~0.50%> Like Nb and Ti, Zr is a carbonitride forming element, and contributes to suppressing grain growth by finely precipitating. To obtain this effect, it is preferable to contain 0.01% or more. On the other hand, excessive content forms intermetallic compounds and reduces the toughness of the steel, so in the present invention, the content is set to 0.50% or less. It is preferably 0.40% or less, and more preferably 0.30% or less.
[0031] <Al:0.01~1.00%> Al is contained as a deoxidizing element and also as an element that improves oxidation resistance, and in order to obtain this effect, it is preferable to contain 0.01% or more. On the other hand, since Al hardens steel by solid solution strengthening and reduces the toughness of steel, the content of Al is set to 1.00% or less in the present invention, preferably 0.60% or less, and more preferably 0.20% or less.
[0032] <Sn:0.01~0.50> Sn is an element that improves corrosion resistance without significantly deteriorating mechanical properties at room temperature, and in order to obtain this effect, it is preferable to contain 0.01% or more. On the other hand, since an excessive content significantly reduces manufacturability, the content is set to 0.50% or less in the present invention, preferably 0.30% or less, and more preferably 0.20% or less.
[0033] <B:0.0002~0.0050%> B is an element that improves workability, especially secondary workability, and in order to obtain this effect, it is preferable to contain 0.0002% or more. On the other hand, since an excessive content reduces weldability and toughness, the content is set to 0.0050% or less in the present invention, preferably 0.0030% or less, and more preferably 0.0015% or less.
[0034] <Ca:0.0002~0.0100%> Ca is an effective element for preventing nozzle clogging that easily occurs during continuous casting, and in order to obtain this effect, it is preferable to contain 0.0002% or more. On the other hand, since Ca easily causes surface defects, the content is set to 0.0100% or less in the present invention, preferably 0.0050% or less, and more preferably 0.0030% or less.
[0035] <Mg:0.0002~0.0100%> Mg is an element that is effective in increasing the equiaxed crystal ratio of the slab and improving workability and toughness, and in order to obtain this effect, it is preferable to contain 0.0002% or more. On the other hand, since excessive content reduces the toughness of the steel and deteriorates the surface properties, the content is set to 0.0100% or less in the present invention, preferably 0.0050% or less, and more preferably 0.0030% or less.
[0036] <REM:0.0002~0.0100%> REM (rare earth elements) are elements that improve oxidation resistance, and in order to obtain this effect, it is preferable to contain 0.0002% or more. On the other hand, since excessive content reduces weldability and toughness, the content is set to 0.0100% or less in the present invention, preferably 0.0080% or less, and more preferably 0.0050% or less.
[0037] In the chemical composition of the present invention, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.
[0038] <Average grain size> The steel sheet according to this embodiment is a steel sheet that has been annealed after hot rolling, and the work structure formed by the hot rolling is recrystallized by annealing, making it possible to adjust the workability and toughness. Here, in this embodiment, in order to ensure toughness as well as workability, it is necessary to adjust the average crystal grain size after recrystallization to 30 μm or less. It may be preferably 25 μm or less. If the average crystal grain size exceeds 30 μm, the toughness decreases and cracks are induced during processing. On the other hand, although there is no particular lower limit for the average crystal grain size, if it is less than 10 μm, there is a risk of the toughness decreasing due to hardening, so it is preferably 10 μm or more. More preferably, it is 15 μm or more. The method for measuring the average crystal grain size is as follows. After colloidal polishing of the L-section of the steel plate (a section perpendicular to the plate width direction), electrolytic polishing was performed to remove polishing distortion, and then an orientation difference map was obtained for the center of the plate thickness by electron backscatter diffraction (EBSD) using a scanning electron microscope. The average crystal grain size was calculated from the orientation difference map by quadrature and the diameter of a circle having the same area as the average crystal grain area. A grain boundary is defined as a boundary with a crystal orientation difference of 15° or more.
[0039] <Thickness> The steel plate according to this embodiment is applied to fastening parts that require high rigidity and high-precision shape control, and needs to be 5 mm or more to ensure rigidity. If it is less than 5 mm, rigidity cannot be ensured, and deformation during use leads to a decrease in sealing performance. On the other hand, although there is no particular upper limit, it is preferable that it is 10 mm or less because it provides workability and toughness and increases the weight of the flange. It is more preferably 9 mm or less, and even more preferably 8 mm or less.
[0040] <Manufacturing method> Next, a method for manufacturing the steel sheet according to the present embodiment will be described. The steel sheet according to the present embodiment can obtain the effects as long as it has the above-mentioned configuration, but can be stably manufactured by, for example, the following manufacturing method.
[0041] Steel having the above chemical composition is melted and a slab is produced by a conventional method. The resulting slab having a thickness of 200 mm is heated and hot rolled. The heating temperature of the slab is usually in the range of 1150 to 1250°C, but 1150 to 1200°C is preferable. The hot rolling is preferably divided into rough hot rolling and finish hot rolling, each of which satisfies the following conditions.
[0042] First, the rough hot rolling is performed by rolling the extracted slab at a total reduction of 80% or more, the final temperature of the rough hot rolling is 1050°C or more, and the interpass time from the completion of the rough hot rolling to the start of the finish hot rolling is preferably 30 to 90 seconds. If the total reduction is less than 80%, the amount of strain to be recrystallized after the rough hot rolling is insufficient, and if it is less than 1050°C, unrecrystallized structures may remain. If the interpass time is outside the above-mentioned range, unrecrystallized or grain growth after recrystallization may occur. By satisfying the above-mentioned rough hot rolling conditions, it is possible to obtain fine and granular recrystallized grains in which the coarse extended grains are broken before the finish hot rolling.
[0043] In the next finish hot rolling, it is preferable that the interpass time after each reduction is 5 seconds or less, the total reduction is 70% or more, the final temperature of the finish hot rolling is 900°C or less, and the coiling temperature is 450°C or less. If the interpass time is more than 5 seconds and the final temperature of the finish hot rolling exceeds 900°C, the processing strain introduced during the finish hot rolling is recovered, and elongated grains tend to remain in the subsequent annealed structure, which may result in coarsening of the average grain size. If the total reduction is less than 70%, elongated grains tend to remain in the subsequent annealed structure, which may result in coarsening of the average grain size.
[0044] After hot rolling, hot-rolled sheet annealing is performed. The hot-rolled sheet annealing conditions are 850°C to 920°C for 1 minute or less, which can produce recrystallized grains of 30 μm or less. In addition, the average heating rate in the temperature range of 400 to 800°C during hot-rolled sheet annealing is preferably 5°C / s or more. If the average heating rate in the temperature range of 400 to 800°C is less than 5°C / s, the processing strain introduced during the finish hot rolling is recovered when passing through the temperature range, and elongated grains tend to remain in the annealed structure thereafter, which may result in coarsening of the average crystal grain size. In addition, pickling may be performed as necessary after hot-rolled sheet annealing.
[0045] The steel sheet of this embodiment will be described more specifically with reference to the following examples, but the present invention is not limited to these examples. EXAMPLES
[0046] Steel having the chemical composition shown in Table 1 was produced by vacuum melting and cast into a mold 200 mm thick, then heated at 1180°C for 2 hours, hot rolled under the hot rolling conditions shown in Table 2, and cooled to 400°C or less to obtain a hot-rolled sheet having a thickness of 5 to 8 mm. The finish hot rolling was performed by adjusting the sheet passing speed so that the interpass time was 3 s or less.
[0047] Next, the hot-rolled sheet was annealed for 30 seconds at the annealing temperature shown in Table 2 to obtain a hot-rolled annealed sheet. In the above annealing, the average heating rate and cooling rate in the temperature range of 400 to 800° C. were all adjusted to be 5° C. / s.
[0048] [Table 1]
[0049] The hot-rolled and annealed sheets obtained above were subjected to the following evaluations.
[0050] <Average grain size> From the hot-rolled annealed sheet obtained above, the L-section of the steel sheet (a section perpendicular to the sheet width direction) was colloidally polished, and then electrolytically polished to remove polishing distortion. Then, the orientation difference map was obtained for the center of the sheet thickness by the electron backscatter diffraction (EBSD) method using a scanning electron microscope, and the average grain size was calculated from the orientation difference map by the quadrature method, and the diameter of a circle having the same area as the average grain area was calculated as the average grain size. The grain boundary is defined as a boundary with a crystal orientation difference of 15° or more.
[0051] <Toughness evaluation by Charpy impact test> To evaluate toughness, a Charpy impact test was performed on the hot-rolled annealed sheet. A V-notch sub-size Charpy impact test piece was prepared from the hot-rolled annealed sheet with the same thickness as the hot-rolled sheet so that the longitudinal direction of the test piece was parallel to the rolling direction. According to the test method described in JIS Z 2242:2018, five pieces were tested at each temperature from 0 ° C to 80 ° C at 20 ° C intervals for each test piece, the brittle fracture rate was measured, the average value of the five brittle fracture rates was calculated, and the average value was organized by test temperature. The temperature at which the brittle fracture rate was 50% was defined as DBTT. From the viewpoint of good toughness, a DBTT of 25 ° C or less was evaluated as a good characteristic.
[0052] <Cross-section hardness after welding> The hardening after welding was evaluated using the cross-sectional hardness of the laser welded part. For the laser welding, hot-rolled annealed sheets of 180 mm in the rolling direction and 50 mm in the width direction were butt-welded without welding wire at a welding speed of 5 m / min and a shielding gas of Ar at a flow rate of 30 L / min. The laser-welded steel sheet was cut at 30 mm intervals perpendicular to the welding direction and embedded in resin so that the cut cross sections were exposed. The exposed cross sections were polished and electrolytically etched, and then the base material part (10 mm from the welded part) and the welded part were measured at the center of the plate thickness. The hardness was measured in accordance with JIS Z 2244:2009 Vickers hardness measurement, and was measured at HV1.0 (9.8 N). Measurements were taken at one point each at five locations on the cross section, and the average value of the base material part and the average value of the welded part were used as the representative value. From the viewpoint of suppressing hardening of the welded joint, an absolute value of the difference between the average value of the base material and the average value of the welded joint of 15HV or less was evaluated as good properties, and an absolute value of 10HV or less was evaluated as even better properties.
[0053] The results of the above evaluations are shown in Table 2.
[0054] [Table 2]
[0055] The hot-rolled annealed steel sheets shown in Table 2 as examples of the present invention satisfy the prescribed composition and average grain size, and therefore are able to achieve both a certain level of toughness and hardening of the welded portion, and have good properties. On the other hand, even in Steels 1 to 6 that satisfy the composition ranges of the present invention, if the average grain size becomes coarse, a certain level of toughness cannot be satisfied. Moreover, in Steels 11 to 14 that fall outside the composition ranges of the present invention, a certain level of toughness and suppression of hardening of the welded portion cannot be achieved at the same time.
Claims
1. The chemical composition, in mass%, is C: 0.002-0.030%, Si: 0.10-1.00%, Mn: 1.0% or less, P: 0.040% or less, S: 0.0300% or less, Cr: 10.0-19.0%, Nb: 0.05-0.15%, Ti: 8 x (C% + N%) ~ 0.40%, N: 0.002-0.030%, Ni: 0 to 0.50%, Mo: 0-2.50% Cu: 0-0.60% V: 0-0.50%, W: 0-0.50%, Co: 0 to 0.50%, Zr: 0 to 0.50%, Al: 0-1.00%, Sn: 0 to 0.50%, B: 0 to 0.0050%, Ca: 0-0.0100%, Mg: 0 to 0.0100%, REM: 0~0.0100% The balance is Fe and impurities. The ferritic stainless steel plate has an average crystal grain size of 30 μm or less and a thickness of 5 mm or more. In the above formula, C% indicates the C content, and N% indicates the N content.
2. Further, in mass%, Ni: 0.01-0.50%, Mo: 0.01~2.50% Cu: 0.01~0.60% V: 0.01-0.50%, W: 0.01-0.50%, Co: 0.01 to 0.50%, Zr: 0.01 to 0.50%, Al: 0.01-1.00%, Sn: 0.01-0.50%, B: 0.0002 to 0.0050%, Ca: 0.0002-0.0100%, Mg: 0.0002 to 0.0100%, REM: 0.0002-0.0100% The ferritic stainless steel sheet according to claim 1, comprising one or more selected from the following:
3. The ferritic stainless steel sheet according to claim 1 or 2, which is a hot-rolled and then annealed sheet.
Citation Information
Patent Citations
High corrosion resistance ferritic stainless steel sheet with excellent toughness, and method of manufacturing the same
JP2011225944A
Ferrite stainless hot-rolled-and-annealed steel sheet and production method for same
WO2020084987A1